International Journal of Mining, Reclamation and Environment - International Journal of Mining, Reclamation and Environment (Taylor & Francis, 2026)
The International Journal of Mining, Reclamation and Environment welcomes mining research papers that explore mining and environmental technology engineering relating to metalliferous deposits, coal, oil sands, and industrial minerals: Design of surface and underground mines, Mine planning and optimization, Mine geomechanics and geotechnical engineering, Artificial intelligence techniques for mining applications, Mining resource estimation and geostatistics, Mining rock excavation technologies Mining automation machinery, Mining environmental impact assessment and permitting, Mining waste management and recycling technologies, Mine reclamation & Acid mine drainage.
FI 0.74
Q3
Keywords: Engineering; Computing & Technology; Ciencia ambiental; Minería; Acuerdos transformativos; Transformative agreements; Ingeniería de minas a cielo abierto y subterráneas, planificación y optimización; Geomecánica minera, tecnología de excavación, automatización e inteligencia artificial; Impacto ambiental, gestión de residuos, drenaje ácido y recuperación de minas